Reference values of gait characteristics in community-dwelling older persons with different physical functional levels - Dapp, Ulrike; Vinyard, Dominic; Golgert, Stefan; Krumpoch, Sebastian; Freiberger, Ellen (BMC Geriatrics, 2022)
BACKGROUND: Mobility is one major component of healthy ageing of older persons. It includes gait speed, nowadays valued as the sixth vital sign of ageing. Quantitative gait analysis can support clinical diagnostics, monitor progression of diseases and provide information about the efficacy of interventions. Fast gait speed is an additional marker in the area of functional ability. Our aim was to contribute reference values of gait parameters of older persons based on their functional ability. METHODS: We visualised and combined three different established frameworks that assess gait characteristics into a new framework based approach that comprises eight gait parameters: gait speed, stride length, walk ratio, single and double support time, step width, step width CV (coefficient of variance), stride length CV. Gait parameters were stratified by two instruments that indicate levels of functional ability: First, the LUCAS Functional Ability Index (FAI), a self-administered screening tool easy to apply to a public-health orientated approach and second the Short Physical Performance Battery (SPPB), an established performance test widely used in comprehensive geriatric assessments (CGA). Gait parameters of older community-dwelling persons were measured with an objective Gait system (GAITRite) across differing functional ability ranging from robust to transient (postrobust and prefrail) to frail physical status. RESULTS: Of 642 community-dwelling participants (age 78.5 ± 4.8; n = 233 male, n = 409 female) categorisations by SPPB were 27.1% for robust (11-12 points), 44.2% for transient (8-10 points), 28.7% for frail (0-7 points), and 16.2, 50.3, 33.5% for robust, transient, frail by LUCAS FAI. Overall, our results showed that distinction by functional level only uncovers a wide spectrum of functional decline for all investigated gait parameters. Stratification by functional ability (biological age) revealed a greater range of differentiation than chronological age. CONCLUSIONS: Gait parameters, carefully selected by literature, showed clinically meaningful differences between the functional featuring a gradient declining from robust over transient to frail in most gait parameters. We found discriminative power of stratifications by SPPB to be the highest, closely followed by LUCAS FAI, age groups and dichotomous age making the application of the LUCAS FAI more cost and time effective than conducting SPPB.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Aged; Frailty; Gait characteristics; community-dwelling; Physical function; Population-based; Prevention; Reference values; Spatiotemporal gait parameters